Analisis Faktor-Faktor yang Mempengaruhi Penerapan Konservatisme Akuntansi (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia tahun 2016-2018) - gusyanto, andre (Jurnal KIAFE, 2020)
The uncertain economic condition in the future has made the company more cautious. One of the financial statements that is based on the prudential principle is the principle of accounting conservatism. Therefore, this study aims to examine and determine the factors that influence the application of accounting conservatism in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018.The sample used in this is manufacturing companies listed on the Indonesia Stock Exchange (BEI) 2016-2018. The sample was selected using purposive sampling so that it resulted in 84 samples which had also been removed from the variable outliers and tested using multiple linear regression test tools with SPSS version 23. The results of this study indicate that the leverage variable has a negative regression coefficient value of -0.100 with a significance value of 0.029 so that the variable Leverage has a negative and significant effect on accounting conservatism so that it is accepted but with the opposite or negative influence. The managerial ownership variable has a positive regression coefficient value of 0.013 with a significance value of 0.044 so that the managerial ownership variable has a positive and significant effect on accounting conservatism. Meanwhile, the variables of capital intensity, firm size, and growth opportunity did not have a significant effect on accounting conservatism. The F test results obtained that the sig F value of 0.045 is smaller than 0.05, so it can be concluded that simultaneously leverage, capital intensity, managerial ownership, company size, and growth opportunity have a significant effect on accounting conservatism.Keywords: Leverage, capital intensity, managerial ownership, firm size, growth opportunity, and accounting conservatismAhmed, A. S., & Duellman, S. (2007). Accounting Conservatism and Board of Director Characteristic: An Empirical Analysis. Journal of Accounting and Economics 43, 411-437.Alfian, A., & Sabeni, A. (2013). Analisis Faktor-Faktor Yang Berpengaruh Terhadap Pemilihan Konservatisme Akuntansi di Indonesia. Diponegoro Journal of Accounting 2 (3), 1-10.Almilia, L. S. (2004). Pengujian Size Hypothesis dan Debt/Equity Hypothesis yang Mempengaruhi Tingkat Konservatisme Laporan Keuangan Perusahaan dengan Teknik Analisa Multinomial Logit. Jurnal Bisnis akuntansi 7(1), 1-19.Ardina, A. M. Y., & Januarti, I. (2012). Penggunaan Perspektif Positive Accounting Theory terhadap Konservatisme Akuntansi di Indonesia. Journal of Accounting 1(1), 1-15.Bahaudin, A., & Wijayanti. (2011). Mekanisme Corporate Governance Terhadap Konservatisme Akuntansi di Indonesia. Dinamika Sosial Ekonomi 7(1).Christiawan, Y. J., & Tarigan, J. (2007). Kepemilikan Manajerial: Kebijakan Hutang, Kinerja, dan Nilai Perusahaan. Jurnal Akuntansi dan Keuangan 9(1).Deviyanti, D. A. (2012). Analisis Faktor-Faktor yang Mempengaruhi Penerapan Konservatisme dalam Akuntansi. (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia). Semarang: Universitas Diponegoro.Fala, D. Y. A. S. (2007). Pengaruh Konservatisme Akuntansi terhadap Penilaian Ekuitas Perusahaan Dimoderasi oleh Good Corporate Governance. Simposium Nasional Akuntansi X. Makasar.Fatmariani. (2013). Pengaruh Struktur Kepemilikan, Debt Convenant, dan Growth Opportunities terhadap Konservatisme pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia. Padang: Universitas Negeri Padang.Febrianti, Maunthe, I. L. S., & Rambe, P. A. (2018). Pengaruh Kepemilikan Institusional, Ukuran Perusahaan, Intensitas Modal, Growth Opportunities, dan Leverage terhadap Konservatisme Akuntansi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016. Retrieved from http://repository.umrah.ac.id/1376/.Feltham, J. Dan Ohlson, J. (1995). Valuation and Clean Surplus Accounting for Operating and Financial Analysis. Contemporary Accounting Research 11, 687-731.Ghozali, I., & Chariri, A. (2016). Teori Akuntansi. Semarang: Badan Penerbit Universitas Diponegoro.Ghozali, I. (2016). Aplikasi Analisis Multivariate dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro.Harahap, Sofyan Syafri. (2012). Analisa Kritis Atas Laporan Keuangan. Jakarta: Grafindo Persada.Hertina, N. R., & Zulaikha. (2017). Analisis Penerapan Konservatisme Akuntansi di Indonesia dalam Perspektif Positive Accounting Theory. Diponegoro Journal of Accounting 6 (3), 1-10.Jensen, M. C., & Meckling, W. H. (1976). Also Published in Foundations of Organizational Strategy. Journal of Financial Economics 3(4), 305"“360.Kiryanto & Suprianto, E. (2006). Pengaruh Moderasi Size terhadap Hubungan Laba Konservatisme dengan Neraca Konservatisme. Simposium Nasional Akuntansi IX. Padang.Lara, et al. (2005). Board of Directors Characteristic and Conditional Accounting Conservatism : Spanish Evidence. European Accounting Review.Mayangsari, S., & Wilopo. (2002). Konservatisme Akuntansi, Value Relevance, dan Discretionary Accruals: Implikasi Empiris Model Feltham Ohlson (1996). Simposium Nasional Akuntansi IV, 685-708.Messier, W. F., Glover, S. M., & Prawitt, D. F. (2014). Jasa Audit and Assurance. Jakarta: Salemba Empat.Oktadella, D. (2011). Analisis Corporate Governance terhadap Integritas Laporan Keuangan. Semarang: Universitas Diponegoro.Oktomegah, C. (2012). Faktor-faktor yang mempengaruhi penerapan konservatisme pada perusahaan manufaktur di BEI. Jurnal Ilmiah Mahasiswa Akuntansi 1 (1), 36-42.Priambodo, M. S., & Purwanto, A. (2015). Analisis Faktor-Faktor yang Mempengaruhi Tingkat Konservatisme Perusahaan-Perusahaan di Indonesia. Diponegoro Journal of Accounting 4 (4), 1-10.Resti. (2012). Analisis Faktor-Faktor yang Mempengaruhi Konservatisme Akuntansi. Makasar: Universitas Hassanudin Makasar.Saputro, J. A., & Setiawati, L. (2004). Kesempatan Bertumbuh dan Manajemen Laba: Uji Hipotesis Political Cost. The Indonesian Journal of Accounting Research 7(2).Sari, C., dan Adhariani, D. (2009). Konservatisme Perusahaan Di Indonesia dan Faktor- Faktor yang Mempengaruhinya. Simposium Nasional Akuntansi XII. Palembang.Savitri, E. (2016). Pengaruh Struktur Kepemilikan Institusional, Debt Convenant, dan Growth Opportunities terhadap Konservatisme Akuntansi. Jurnal Al-Iqtishad 1(12), 39-54.Septian, A., & Anna, D. (2014). Pengaruh Kepemilikan Manajerial, Ukuran Perusahaan, Debt Convenant, dan Growth Opportunities terhadap Konservatisme. Jurnal Fakultas Ekonomi dan Bisnis 1(3).Sinambela, M. O. E., & Almilia, L. S. (2018). Faktor-Faktor yang Mempengaruhi Konservatisme Akuntansi. Jurnal Ekonomi dan Bisnis 21(2), 289-312.Sudana, I. M. (2015). Manajemen Keuangan (Teori dan Praktik). Surabaya: Airlangga University Press.Utami, R. F. (2011). Influence Risk of The Litigation and The Financial Distress Company"™s Accounting Conservatism. Bandung: Universitas Komputer Indonesia.Watts, R. L. (2003). Conservatism in Accounting part I: Explanations and Implications. Journal of Accounting and Economics, 207-221.Watts, R. L., & Zimmerman, J. L. (1986). Possitive Accounting Theory: A Ten Year Perspective. The Accounting Review 65 (1), 131-157.Watts, R. L., & Zimmerman, J. L. (1986). Positive Accounting Theory. New York: Prentice Hall.Widya. (2005). Analisis Faktor-Faktor yang Mempengaruhi Pilihan Perusahaan Terhadap Akuntansi Konservatif. Simposium Nasional Akuntansi VII Denpasar, 709-724.Wimelda, L. & Marlinah, A. (2013). Variabel-Variabel yang Mempengaruhi Struktur Modal pada Perusahaan Publik Sektor Non Keuangan. Jurnal Akuntansi 5(3), 200-213.Zhang, J. (2007). The Contracting Benefits of Accounting Conservatism to Lenders and Borrowers. Journal of Accounting and Economics 45, 27-54.